Hazardous Home-Based Sub-Contracted Work : A Study of Multiple Tiered Exploitation - Khan, Shahrukh Rafi : Khattak,Saba Gul and Kazmi, Sajid (Karachi,Pakistan Oxford University Press, 2005)
This book investigates various dimensions of exploitation of sub-contracted home-based workers engaged in hazardous work. It explores the exploitation of children, particularly girls, and women in the chain. There is a particular focus on the negative health impacts of such work and on public policies that can bring about a positive change.
Include Index
Keywords: Women employees -- Pakistan--Karachi -- Child labor